Transparency in the Management of School Operational Assistance Funds through the Implementation of the School Activity and Budget Plan Application - Tri Prasetyo Handayani; Nur Khoiri; Ghufron Abdullah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study explores the transparency of School Operational Assistance fund management via the School Activity and Budget Plan Application at SD St Antonius 02 Semarang. Focusing on information disclosure, data access, clarity, constraints, and public trust, this qualitative case study collected data through in-depth interviews, observations, and documentation from purposively selected participants: the principal, treasurer, asset officer, teachers, and school committee. Data were analyzed thematically. Findings reveal that transparency is practiced through meeting disseminations, School Activity and Budget Plan Application reporting, and internal involvement. However, detailed document access remains limited, information clarity for non-managers is suboptimal, and technical, human resource, and organizational constraints persist. Despite these limitations, stakeholder trust remains high due to consistent communication and accountable practices. Ultimately, while School Activity and Budget Plan Application significantly enhances structured financial governance, achieving true participatory transparency requires more communicative information delivery and broader stakeholder engagement.